2006
DOI: 10.1007/s10582-006-0456-0
|View full text |Cite
|
Sign up to set email alerts
|

Study of plasma—solid interaction in electronegative gas mixtures

Abstract: Low-temperature reactive plasmas employing electronegative gases are often used in modern technologies. Negative ions in such plasmas affect the transport of charged species and in this way influence the processes in the boundary layer between plasma and surface of metal substrate or probe. The contribution presents results of the computer experiment describing the interaction of electronegative plasma with immersed substrates. The method of solution was the particle simulation technique and several approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The calculations were performed in the pressure range 13.3 to 1330Pa. The physical results can be found in our papers [5,7,8].…”
Section: Computer Experiments --Self-consistent Pic-mc Techniquementioning
confidence: 85%
See 1 more Smart Citation
“…The calculations were performed in the pressure range 13.3 to 1330Pa. The physical results can be found in our papers [5,7,8].…”
Section: Computer Experiments --Self-consistent Pic-mc Techniquementioning
confidence: 85%
“…These measurements were performed in our laboratory for many years --see e.g. [3][4][5]. The measurements were performed at low and medium pressures ranging from 67 to 800 Pa and the following plasma characteristics were obtained: concentration and temperature of electrons, intensity of axial electric field and the collision frequency.…”
Section: Computer Experiments --Self-consistent Pic-mc Techniquementioning
confidence: 99%
“…Among others, it has been already found that such additions, which play a role of electronegative gases, to noble gas plasma bring about an evident decrease in the plasma density. [20] Of course, it should result in the lower density of free radicals generated on the surface. Accordingly, the final peel strength after the plasma-needle treatment of the SBS surface is a resultant of two key factors: the density of free radicals created by plasma and the yield of their reactions forming the functionalities responsible for the chemical adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…First, we should take into account the fact that the addition of O 2 or CO 2 to helium is not only a source of species for the creation of oxygen functionalities on the polymer surface, but they also drastically change the plasma conditions. Among others, it has been already found that such additions, which play a role of electronegative gases, to noble gas plasma bring about an evident decrease in the plasma density 20. Of course, it should result in the lower density of free radicals generated on the surface.…”
Section: Resultsmentioning
confidence: 99%